Multicriteria Decision Support Model for Selection of Fiberglass Suppliers - Rodrigues, Celina (2022)
This chapter presents a real case of a decision problem in supplier selection of one of the main raw materials of a wind blades industry. The study considered all currently qualified suppliers according to considerably rigorous standards and specifications and one in qualification process. It is a complex choice, given the strategic importance of the product and the multiplicity of criteria to be considered, both quantitative and qualitative. The strong competitiveness requires a special attention which concerns the supplier selection; not only the price matters; in fact, a day of stoppage due to failure in a delivery, for example, corresponds to high losses that would have justified the purchase from a supplier with a higher price but with no delivery failures. In order to contribute to the problem resolution, the methodologies PROMETHEE and AHP were applied, whose results allow the authors to stablish a ranking of the considered suppliers. The results will support the company on the selection of fiberglass suppliers and in some cases clarify where they can find the main trade-offs.